2012
DOI: 10.1093/infdis/jis183
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Domain Membrane Proximal External Region but Not Surface Unit–Directed Broadly Neutralizing HIV-1 Antibodies Can Restrict Dendritic Cell–Mediated HIV-1 Trans-infection

Abstract: Anti-gp41 bNAbs have the potential to inhibit mDC-mediated HIV-1 infection because they bind plasma membranes prior to the formation of an infectious synapse, positioning them to neutralize subsequent virus transfer. As opposed to gp120-directed antibodies, anti-gp41 bNAbs might prevent HIV-1 infection if transmission or spread at the initial site of invasion occurs from a DC-associated source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 50 publications
3
39
0
Order By: Relevance
“…Indeed, the activity of 10E8 and 2F5 was negligible against YU2 Env even at the highest concentration used (50 g/ml). The reduced activity of MPER bNMAbs against VS-mediated transmission was unchanged in experiments using a commercially available Fc blocking reagent (data not shown), suggesting that loss of function was not related to Fc receptor binding, in line with previous data (45). We hypothesized that steric inhibition reduces the on-rate of MPER bNMAbs for their epitopes, since they are sandwiched between the base of gp120 and the viral lipid envelope.…”
Section: Mdm Transmit a High-multiplicity Infection To T Cells Acrosssupporting
confidence: 79%
See 1 more Smart Citation
“…Indeed, the activity of 10E8 and 2F5 was negligible against YU2 Env even at the highest concentration used (50 g/ml). The reduced activity of MPER bNMAbs against VS-mediated transmission was unchanged in experiments using a commercially available Fc blocking reagent (data not shown), suggesting that loss of function was not related to Fc receptor binding, in line with previous data (45). We hypothesized that steric inhibition reduces the on-rate of MPER bNMAbs for their epitopes, since they are sandwiched between the base of gp120 and the viral lipid envelope.…”
Section: Mdm Transmit a High-multiplicity Infection To T Cells Acrosssupporting
confidence: 79%
“…7C and D). Thus, the MPER region appears to be particularly susceptible to steric restriction at the macrophage-to-T cell VS, although Env sequence-dependent effects on neutralization efficacy also need to be taken into account (45).…”
Section: Mdm Transmit a High-multiplicity Infection To T Cells Acrossmentioning
confidence: 99%
“…Interestingly, a similar inhibitory activity of VRC01 was recently reported for the HIV-1 transmission from macrophages to T cells (43). In contrast, Abela et al and Sagar et al found that VRC01 did not block cell-mediated HIV-1 transmission from HIV-1-infected PBMC or mature MoDC to TZM-bl target cells and proposed that cell-to-cell transmission enabled HIV-1 to evade inhibition by anti-gp120 Ab (44,45). Several mechanisms might be explained by the different findings observed.…”
supporting
confidence: 57%
“…ing a luciferase gene in place of the Nef open reading frame [ORF]) and HIV NL4-3 have been described previously (58,59). To create an envelope glycoprotein (GP)-deficient NL4-3 provirus plasmid carrying the intact Nef ORF (NL4-3⌬env), the Env ORF containing deletions in the env sequence of NL4-3.Luc.R…”
mentioning
confidence: 99%